Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have the following question:

Show that $\displaystyle\sum_{k=1}^n a_k=na_n-\displaystyle\sum_{k=1}^{n-1} k(a_{k+1}-a_k)$

then evaluate $\displaystyle\sum_{k=1}^n \lfloor \log_2(k) \rfloor=(n+1)\lfloor \log_2(n) \rfloor -2^{\lfloor \log_2(n) \rfloor+1}+2$

I can show the first part pretty easily by induction but I have no idea where to go with the second part. I use the expansion and get:

$\displaystyle\sum_{k=1}^n \lfloor \log_2(k) \rfloor=n\lfloor \log_2(n) \rfloor-\displaystyle\sum_{k=1}^{n-1} k(\lfloor \log_2(k+1) \rfloor-\lfloor \log_2(k) \rfloor)$ but I have no idea where to go from here

Thanks for any help

share|cite|improve this question
up vote 2 down vote accepted

You (now) have

$$\sum_{k=1}^n\lfloor\lg n\rfloor=n\lfloor\lg k\rfloor-\sum_{k=1}^{n-1}k\Big(\lfloor\lg(k+1)\rfloor-\lfloor\lg k\rfloor\Big)\;,$$

where I use $\lg$ for $\log_2$. Now notice that when $2^m\le k<k+1<2^{m+1}$, $\lg k=\lg(k+1)$, and the corresponding term in the last summation is $0$. You get a non-zero term only when $k=2^m-1$ for some $m$, and in that case the term that you get is $k$. Thus,

$$\sum_{k=1}^{n-1}k\Big(\lfloor\lg(k+1)\rfloor-\lfloor\lg k\rfloor\Big)=\sum_{1\le m\le\lg n}\left(2^m-1\right)=\sum_{m=1}^{\lfloor\lg n\rfloor}\left(2^m-1\right)\;.$$

From here you should be able to finish it; it’s just a little algebra now.

share|cite|improve this answer

If you explicitly write out the first several terms in your second summation $\sum_{k=1}^{n-1}k(\lfloor \log_2(k+1)\rfloor - \lfloor \log_2(k)\rfloor)$, you will find out all terms are zero except when $k=2^s-1$ where $s$ is an integer less than $\lfloor \log_2(n)\rfloor$. Then it becomes a geometrical series and it's easy to sum it up and get a nice result.

share|cite|improve this answer

You are asked to show first

$$ \displaystyle\sum_{k=1}^n a_k=na_n-\displaystyle\sum_{k=1}^{n-1} k(a_{k+1}-a_k) \,.$$

To prove this you need to use summation by parts

$$ \sum_{k=m}^n f_k(g_{k+1}-g_k) = \left[f_{n+1}g_{n+1} - f_m g_m\right] - \sum_{k=m}^n g_{k+1}(f_{k+1}- f_k)\,. $$

In your case, let $f_k=a_k$ and $g_k=k \Rightarrow g_{k+1}-g_k=1$.

share|cite|improve this answer
I'm pretty sure that I can just use induction to show this? – hmmmm Sep 29 '12 at 15:02

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.